CCR5/CD4/CXCR4 oligomerization prevents HIV-1 gp120(IIIB) binding to the cell surface - Martínez-Muñoz, Laura (National Academy of Sciences, 2014)
CCR5 and CXCR4, the respective cell surface coreceptors of R5 and X4 HIV-1 strains, both form heterodimers with CD4, the principal HIV-1 receptor. Using several resonance energy transfer techniques, we determined that CD4, CXCR4, and CCR5 formed heterotrimers, and that CCR5 coexpression altered the conformation of both CXCR4/CXCR4 homodimers and CD4/CXCR4 heterodimers. As a result, binding of the HIV-1 envelope protein gp120(IIIB) to the CD4/CXCR4/CCR5 heterooligomer was negligible, and the gp120-induced cytoskeletal rearrangements necessary for HIV-1 entry were prevented. CCR5 reduced HIV-1 envelope-induced CD4/CXCR4-mediated cell-cell fusion. In nucleofected Jurkat CD4 cells and primary human CD4(+) T cells, CCR5 expression led to a reduction in X4 HIV-1 infectivity. These findings can help to understand why X4 HIV-1 strains infection affect T-cell types differently during AIDS development and indicate that receptor oligomerization might be a target for previously unidentified therapeutic approaches for AIDS intervention.